Efficacy of novel organotin(IV) complexes on non-durable tropical wood against decay fungi - Md. Masudur, Rahman; Ismail, Jusoh; Md. Abu, Affan; Ahmad, Husaini; Sinin, Hamdan (Springer, 2013)
Interest in organotin(IV) compounds is increasing due to their interesting structural features and possession of biological activities. The objective of this study was to determine the efficacy of novel organotin(IV) complexes against Trametes versicolor and Gloeophyllum trabeum decay fungi. Soil block decay test was performed using T. versicolor and G. trabeum for 16 weeks. Ten 19 9 19 9 19 mm3 sized wood cubes of Alstonia scholaris, Macaranga triloba and Hevea brasiliensis were treated with three levels of concentration (0.1, 0.5 and 1 %) of monomethyltin(IV) (MMT) and monophenyltin(IV) (MPT) of monosubstituted organotin(IV) and dimethyltin(IV) (DMT),diphenyltin(IV) (DPT) and dibutyltin(IV) (DBT) of disubstituted organotin(IV) complexes with 2-acetylpyridine-N(4)-cyclohexyl thiosemicarbazone (APCT) ligand and their respective retention uptake was determined. The best protection against decay fungi was provided by dibutyltin(IV) complex followed by diphenyltin(IV),dimethyltin(IV), monophenyltin(IV) and monomethyltin(IV)complexes with mean weight loss ranging from 4 to 5, 5 to 7,8 to 9, 10 to 11 and 14 to 19percent, respectively while theweight loss of the untreated wood cubes varied from 51 to65 %. Wood densities decreased with increased weight loss.Density reduction of monosubstituted organotin(IV) treated wood cubes was higher than disubstituted organotin(IV) treated wood cubes. Soil block test showed that selected organotin(IV) complexes are effective and among all of them dibutyltin(APCT) complex gave the best protection against the tested T. versicolor and G. trabeum decay fungi.